Agency Theory and Variable Pay Compensation Strategies - Stroh, Linda K.; Brett, Jeanne M.; Baumann, Joseph P.; Reilly, Anne H. (Academy of Management Journal, 1996)
This study used a sample of middle-level managers to investigate the effects of organization-level agency-theory-based variables on the proportion of variable compensation that managers receive. Level of task programmability was associated with an increased use of variable pay, and long-term relationships between an agent and principal were associated with decreased use. Results supported the classical organization-theory prediction that under higher risk, organizations use higher proportions of variable pay; hut results question agency theory's ability to predict compensation strategy for middle-level managers in the high-risk situation.